Fracture Phenomena In Soda Lime Silica Glass Caused By Bullet Impacts - Daud, Sharifah Mastura Syed Mohd (2012)
A series of studies was performed under controlled experimental conditions to investigate the fracture patterns produced in static loading (ball dropping experiments) and also the impacts of bullets of different calibres and nose shapes, fired from different weapons, onto soda lime silica glass of different dimensions and thicknesses. The results obtained in static loading experiments confirmed the earlier findings reported in the literature. In the bullet induced glass fracture experiments, all the bullets were fully metal jacketed except .38 in.